A study of the contribution of some cognitive abilities and the level of performance of the volleyball spike skill for third-year students in the College of Physical Education and Sports Sciences, University of Baghdad - Salman, Mustafa Mahdi; Jawda, Murtaza Ali; Ali, Mustafa Najdat Muhammad (Sulaimani Journal for Humanities, 2025)
The research aims to identify the correlation relationship and the percentage of the contribution of some sensory-motor abilities and the level of performance of some basic skills in volleyball for Third stage students at the Faculty of physical education and Sports Sciences, University of Baghdad, and the assumption of the research that there is a statistically significant correlation between some cognitive abilities and the level of performance of some volleyball skills for Third stages tudents of the Faculty of physical education and Sports Sciences, University of Baghdad, and to identify the proportions of the contribution of some cognitive abilities to the level of performance with volleyball skills, as the descriptive method was used to fit the research sample, which was conducted on a group of third-stage students the number of(30) students from the total The researcher concluded through the results that the correlation between some sensory-motor abilities and the level of skill performance in volleyball (weak), as well as in order to identify the points (strengths) and the reasons for the development of the technical level of students by knowing the contribution ratios of the studied variables.